An incremental usability and accessibility evaluation framework for digital libraries - King, Neil; Hoi-Yan Ma, Terry; Zaphiris, Panayiotis; Petrie, Helen; Hamilton, Fraser (My University, 2004)
This paper presents an incremental usability and accessibility framework for evaluating digital libraries. The results obtained from a case study, where four Joint Information Systems Committee (JISC) services were evaluated, are also presented. The applicability of the framework to similar evaluations is identified.